Archbishop Anselm 1093–1109: Bec Missionary, Canterbury Primate, Patriarch of Another World. By Sally N. Vaughn - Ward, Benedicta (The journal of theological studies, 2013)
It is unfair to begin with a negative, as I was tempted to do on opening Professor Vaughn’s new study of Anselm. The history of her correspondence with Sir Richard Southern is still too close to my thoughts for me to be sure of being impartial and fair. I must, however, protest about her assertion that Saint Anselm: A Portrait in a Landscape was, ‘as Southern states in his preface, written in response to and indeed was inspired by my own book’ (p. xvi). This is very far from the comment she is referring to, which states that ‘the works of Professor Sally Vaughn and Dr Walter Frohlich have been a frequent stimulus to further thought’ (Saint Anselm: A Portrait in a Landscape, p. xvii).